Islam Dan Pergerakan Civil Society Kebudayaan Transnasional Hizmet Di Indonesia - Ozi Setiadi (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2017)
Islam Dan Per The conclusion of this study is that Islam is a religion that became one of the cultural resources contribute to the strengthening of civil society, so that religion becomes a media that plays an important role in widening the public sphere and are in a position that is in line with the civil society. The truth of this conclusion is supported by a number of findings related to the research object, which Hizmet movement in Indonsia as one Muslim civil society. First, the Hizmet movement in Indonesia as a transnational civil society movement that carries the Islamic themes emerged and developed in Indonesia using a cultural approach as their collective agenda. This movement has a set of economic independence through business people, improve education through cultural criticism, and make the dialogue as a means for conflict resolution and brotherhood. Second, is the Hizmet movement ideology ( services ), which adopts the ideology of Islamic values. This ideology popularized by Fethullah Gülen and followed by those who were inspired by his thoughts, and then establish a culture of civil society movement known as Hizmet movement. This ideology promoting ignorance, poverty, and conflict as a common enemy that must be fought. Third, ignorance, poverty, and conflict into a separate reference to the Hizmet movement in performing services for the humanitarian movement. This transnational movement then set up humanitarian agencies. It also became its own model and characterizes the movements which promote dialogue and tolerance. In Indonesia, this movement has established educational institutions, social institutions, economic institutions, and the relationship between universities. They joined in PASIAD Indonesian, Turkish Indonesian Trade Association ( TITA ), Fethullah Gülen Chair, and dershane. The existence of this growing movement and can be seen from the distribution that have established humanitarian agencies in major cities in Indonesia. It became the Hizmet movement efforts in building a civil society in Indonesian culture, and to prove that Islam is in line with the civil society.